Qualtrics survey screeners for online focus groups_Domestic hydrogen acceptance 2022.docx - Gordon, Joel; Balta-Ozkan, Nazmiye; Nabavi, Seyed Ali (Cranfield University, 2022)
The file provides the full versions of six unique screening surveys built in Qualtrics as part of the recruitment process for a series of online focus groups, conducted between February and April 2022. The content shows all questions as well as the filtering process. The surveys were designed to recruit against six specific groups: Renewable energy communities; smart homes and solar homes; environmentally engaged; technology engaged; industrial towns; fuel poor; and a baseline group excluding all previous specifications. The project is part of a study exploring consumer perceptions of domestic hydrogen for home heating and cooking, and social acceptance levels across different consumer groups and demographics.
Keywords: 'Survey screeners'; 'Focus groups'; 'Qualtrics'; 'Online questionnaire'; 'Hydrogen heating and cooking'; 'Consumer heterogeneity'